(3aJM GdHGQi HTQM UMjM GdHNGQis - (3CMeO Hf Ydj Hf eMeO Hf MLQ GdTGaYj GdcfGfj GdYSbdGfj, TgGH GdOjf CHh GdaVd, GHf MLQ, J (B852 (3g` s; (3CHh YHO Gddg eMeO Hf GdMSf Hf aQbO, GdTjHGfj,J (B189 (3g` s ((3eMeO Hf YHO GdQMje Hf eMeO Hf YHO dGdg Hf CHj GdNjQ GdNRQLi GdCfUGQi GdSYOi GdSGYOi s)
(3ChdgG (B:s
(3jHOC HcJGH GdUhe cPG ddCcKQ , hai QhGjI GdfSai cJGH GdUjGe (B" s
(3BNQgG (B:s
(3BNQg ef HGH GdefGbH bhdg (B:" (3hbO JbOe ai GdJeje ai GdcdGe Ydi MOjK YeQGf ai bUI GdeQCI UGMHI GdeRGOJjf eGjJYdb Hchfg Udi Gddg Ydjg hSde cGf JfGe YjfGg hdG jfGe bdHg adjQGLY efg ef CQGO Gdhbha Ydjg s
(3HgG fXGe GdJYbjHIs
(3LRA BNQ efgs
(3cJHJ YfGhjjf dcJH hGdCHhGH HGdMeQIs
(3YdjgG JedcGJ GbOegG SfI (B1039 (3g` HGSe eMeO Ydi Hf YdGf GdHcQi GdUOjbi GdTGaYi s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdMOjK h GdeUWdMs